Efficacy and Safety of Ultrasound-Guided versus Fluoroscopy-Guided Percutaneous Nephrolithotomy in Children: A Systematic Review and Meta-Analysis - Muhammad Reza Amara Taqwa; Muhammad Farrell Rikhad; Roy Dwi Antariksa Kristanto; Hinggil Addin Ilmana Punto Baskoro (Brawijaya Journal of Urology, 2026)
Introduction. Ultrasound-guided percutaneous nephrolithotomy (PCNL) is a radiation-sparing alternative to conventional fluoroscopy-guided PCNL in children, yet pediatric evidence remains limited. This systematic review and meta-analysis evaluated the efficacy and safety of both modalities in pediatric patients. Methods. Following PRISMA 2020 guidelines, PubMed, Embase, and Scopus were searched from inception to March 3, 2026. Comparative studies evaluating ultrasound-guided versus fluoroscopy-guided PCNL in children were included. Three reviewers independently performed study selection, data extraction, and quality assessment. Risk of bias was evaluated using the Cochrane Risk of Bias 2 tool for randomized controlled trials and the Newcastle-Ottawa Scale for non-randomized studies. Meta-analyses were performed in RStudio using a random-effects model with restricted maximum likelihood estimation and Hartung-Knapp-Sidik-Jonkman adjustments. Result. Five comparative studies involving 300 pediatric patients (136 ultrasound-guided; 164 fluoroscopy-guided) were included. There was no significant difference between groups in stone-free rate (RR 0.99, 95% CI 0.90–1.09; I²=0.0%) or overall complication rate (RR 0.82, 95% CI 0.29–2.28; I²=66.4%). Ultrasound guidance was associated with reduced fluoroscopy screening time (SMD -1.48, 95% CI -2.97 to 0.00; I²=88.8%). No significant differences were observed in operative time, puncture/access time, or radiation dose. Conclusion. Ultrasound-guided PCNL demonstrates comparable efficacy and safety to fluoroscopy-guided PCNL in children while reducing fluoroscopy exposure. Further prospective multicenter randomized studies are needed to confirm these findings.